2023
DOI: 10.3390/foods12132538
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Reduce the Occurrence of Egg Translucency and Its Effect on Bacterial Invasion

Abstract: Translucent egg consumption is low due to consumer acceptance and quality concerns, which is a problem that egg producers need to address. This study was performed to evaluate the reasons for the high occurrence of egg translucency in summer, as well as whether the addition of mono-dicalcium phosphate (MDCP) to the diet can relieve eggshell translucency and whether eggshell translucency is associated with the risk of bacterial invasion. A total of 72 laying hens that were 36 weeks old were randomly divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…No significant differences were found between the T H and T L groups, which align with previous research, where no significant differences in the mastoid space area were observed among the various eggshell translucency groups ( P < 0.01). Additionally, eggshell membrane thickness in the T H group was significantly higher than that in the T L group ( P < 0.01), consistent with prior studies ( Shi et al, 2023 ). Interestingly, when examining the X-ray image samples, it was noted that in the T H group, many mastoid cores were located on the inner side of the eggshell membrane (i.e., within the internal region of the egg).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…No significant differences were found between the T H and T L groups, which align with previous research, where no significant differences in the mastoid space area were observed among the various eggshell translucency groups ( P < 0.01). Additionally, eggshell membrane thickness in the T H group was significantly higher than that in the T L group ( P < 0.01), consistent with prior studies ( Shi et al, 2023 ). Interestingly, when examining the X-ray image samples, it was noted that in the T H group, many mastoid cores were located on the inner side of the eggshell membrane (i.e., within the internal region of the egg).…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have employed SEM to observe the microstructure of eggshells. Each SEM image sample is typically around 500 μm in size, enabling accurate measurements of mastoid space height and width, thus providing a reliable microscopic foundation for understanding the formation of eggshell translucency ( Wang et al, 2017 ; Shi et al, 2023 ). However, the eggshell is a 3-dimensional entity, constituted by a complex interplay of spatial dimensions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, three evaluators compare the eggs to these standard images. An egg is classified as having a particular level of translucency when two evaluators provide a consistent evaluation level ( Shi et al, 2023 ). The grading standards for manual evaluation methods vary ( Figure 1 ), ranging from level 3 to level 6, and there is no unified classification ( Holst et al, 1932 ; Chousalkar et al, 2010 ; Wang et al, 2019 ; Shi et al, 2023 ).…”
Section: Evaluation Methods For Translucent Eggsmentioning
confidence: 99%
“…However, pink eggs often have eggshell translucency, which reduces their overall appearance quality ( Zhang et al, 2021 ). As a result, the decrease in egg quality leads to a decrease in consumers’ purchasing intention and significant economic losses for the egg production industry ( Shi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%